International School Teacher Pedagogy in Managing the Behavior of Students from Different Cultures - Oktosiyanti MT. Abdullah; Mukhtar Yusuf (Universitas Pendidikan Ganesha, 2026)
The low ability of teachers to manage student behavior impacts the effectiveness of learning. The urgency of improving teachers' pedagogical competence in behavior management creates a conducive and inclusive learning atmosphere. The aim is to analyze the level of knowledge and skills of teachers in managing student behavior based on gender, age, and race variables. The quantitative approach method with a survey design of 160 teachers internationally. Data were collected through a Likert scale questionnaire (1–5) and analyzed using descriptive statistics, t-tests, and One-Way ANOVA with the help of SPSS 29.0. The results show a high level of teacher knowledge (average 4.71 out of 5), with significant differences based on gender (t = 2.621; p = 0.011), but not significant based on age (F = 0.563; p = 0.802) or race (F = 3.356; p = 0.190). The findings highlight the importance of ongoing training in positive behavior management. Conclusion: Improving teacher competence through training and strengthening learning modules is key to the effectiveness of student behavior management. Implications: Schools need to develop behavior management training policies based on inclusive practices.